2021
DOI: 10.1038/s41586-020-03144-0
|View full text |Cite
|
Sign up to set email alerts
|

IgA transcytosis and antigen recognition govern ovarian cancer immunity

Abstract: Most ovarian cancers are infiltrated by prognostically relevant activated T cells1–3, yet exhibit low response rates to immune checkpoint inhibitors4. Memory B cell and plasma cell infiltrates have previously been associated with better outcomes in ovarian cancer5,6, but the nature and functional relevance of these responses are controversial. Here, using 3 independent cohorts that in total comprise 534 patients with high-grade serous ovarian cancer, we show that robust, protective humoral responses are domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 31 publications
1
96
1
Order By: Relevance
“…Ig is a well-known molecule essential for the humoral immune response, but its roles in tumorigenesis are far from clear. Some studies have elucidated the effects of Ig on B cell infiltration in the tumor microenvironment, but many phenomena are still difficult to understand from the perspective of B cell-derived Ig (105)(106)(107). The identification of cancer-derived Ig is undoubtedly a significant finding in the current research area of Ig and largely improves the understanding of Ig in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ig is a well-known molecule essential for the humoral immune response, but its roles in tumorigenesis are far from clear. Some studies have elucidated the effects of Ig on B cell infiltration in the tumor microenvironment, but many phenomena are still difficult to understand from the perspective of B cell-derived Ig (105)(106)(107). The identification of cancer-derived Ig is undoubtedly a significant finding in the current research area of Ig and largely improves the understanding of Ig in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer and hepatocellular carcinoma, IgAproducing plasma cells have been shown to function as potent immunosuppressive cell populations through the expression of IL-10 and PD-L1 (Shalapour et al, 2015(Shalapour et al, , 2017. On the other hand, in ovarian cancer, a recent report demonstrated that protective humoral responses are dominated by the production of polyclonal IgA, which binds to polymeric IgA receptors universally expressed on the tumor cells (Biswas et al, 2021). Interestingly, IgA responses were shown to impair ovarian cancer growth through complementary mechanisms: antigen-specific IgA redirected myeloid cells against cell-surface antigen-positive tumor cells, while transcytosis of non-antigen-specific IgA by tumor cells induced broad transcriptional changes, including the upregulation of IFN-γ receptors and several DUSP phosphatases, which antagonize the RAS pathway.…”
Section: Anti-tumor Role Of Tls B Cellsmentioning
confidence: 99%
“…The immune system plays a complex role in the tumor microenvironment. In some instances, the immune system has been implicated in promoting the growth and metastatic capacity of malignant cells, while in other instances, the innate and adaptive immune branches have eradicated malignant cells thereby preventing tumor growth 154‐161 . This duality has been explored in studies specifically investigating the heterogeneity of B cells and PC in human malignancies over the last few years, with more recent data exploring IgA + PC in cancer.…”
Section: Effector Sites For Iga+ Plasma Cells During Inflammationmentioning
confidence: 99%